Abnormal Subcortical Brain Morphology in Patients with Knee Osteoarthritis: A Cross-sectional Study - Mao, Cui Ping; Bai, Zhi Lan; Zhang, Xiao Na; Zhang, Qiu Juan; Zhang, Lei (Frontiers in Aging Neuroscience, 2016)
Despite the involvement of subcortical brain structures in the pathogenesis of chronic pain and persistent pain as the defining symptom of knee osteoarthritis (KOA), little attention has been paid to the morphometric measurements of these subcortical nuclei in patients with KOA. The purpose of this study is to explore the potential morphological abnormalities of subcortical brain structures in patients with KOA as compared to healthy control subjects by using high resolution MRI. Structural MRI data were acquired from 26 patients with KOA and 31 demographically similar healthy individuals. The MR data were analyzed by using FMRIB's integrated registration and segmentation tool (FIRST). Both volumetric analysis and surface-based shape analysis were performed to characterize the subcortical morphology. The normalized volumes of bilateral caudate nucleus were significantly smaller in the KOA group than in the control group (P = 0.004). There was also a trend toward smaller volume of the hippocampus in KOA as compared to the control group (P = 0.027). Detailed surface analyses further localized these differences with a greater involvement of the left hemisphere (P < 0.05, corrected) for the caudate nucleus. Hemispheric asymmetry (right larger than left) of the caudate nucleus was found in both KOA and control groups. Besides, no significant correlation was found between the structural data and pain intensities. Our results indicated that patients with KOA had statistically significant smaller normalized volumes of bilateral caudate nucleus and a trend toward smaller volume of the hippocampus as compared to the control subjects. Further investigations are necessary to characterize the role of caudate nucleus in the course of chronicity of pain associated with KOA.